(untitled) (Bangladesh Critical Care Journal, 2024)
Peripartum cardiomyopathy (PPCM) is a rare but life-threatening disease in later stages of pregnancy. PPCM presents in the last month of pregnancy or within five months of puerperium in the absence of pre- existing heart disease. It remains a poorly understood entity and its management remains a topic of debate. Although majority recovers, long-term morbidity is quitecommon. Peripartum discomforts often mask and delay the diagnosis of PPCM. Unavailability of previous cardiac imaging is rather common and this makes the diagnosis even more complicated. Early and aggressive management towards reducing preload show evidence of better outcome. Here we report a case of PPCM presenting to us diagnosed after Caesarean Section followed by Grand mal seizure. Bangladesh Crit Care J September 2024; 12 (2): 163-166